2016
DOI: 10.1063/1.4946784
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy enhanced formation and phase transition of Cu-rich precipitates in α - iron under neutron irradiation

Abstract: In this paper, we employed both molecular statics and molecular dynamics simulation methods to investigate the role of vacancies in the formation and phase transition of Cu-rich precipitates in α-iron. The results indicated that vacancies promoted the diffusion of Cu atoms to form Cu-rich precipitates. After Cu-rich precipitates formed, they further trapped vacancies. The supersaturated vacancy concentration in the Cu-rich precipitate induced a shear strain, which triggered the phase transition from bcc to fcc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Thus, it is very important to understand the effect of vacancy on Cu precipitation behavior in HSLA steel during the aging process, in order to improve the mechanical properties of HSLA steel and to design and develop new high-quality HSLA steel grades. Lv et al [ 9 ] studied the effect of vacancy in BCC (body-centered cubic)-Fe on Cu atom precipitation during aging by using the molecular dynamics (MD) method. They found that the presence of vacancies will expand the diffusion coefficient of Cu atoms and promote the formation of Cu precipitates containing twin boundary and stacking faults of the FCC structure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is very important to understand the effect of vacancy on Cu precipitation behavior in HSLA steel during the aging process, in order to improve the mechanical properties of HSLA steel and to design and develop new high-quality HSLA steel grades. Lv et al [ 9 ] studied the effect of vacancy in BCC (body-centered cubic)-Fe on Cu atom precipitation during aging by using the molecular dynamics (MD) method. They found that the presence of vacancies will expand the diffusion coefficient of Cu atoms and promote the formation of Cu precipitates containing twin boundary and stacking faults of the FCC structure.…”
Section: Introductionmentioning
confidence: 99%